Lymphedema a concise compendium of theory and practice - Lee, Byung-Boong; Bergan, John J. 1927-2014; Rockson, Stanley G. (Springer London, 2011)
Lymphedema: A Concise Compendium of Theory and Practice brings into one volume the most important sources of information to guide the evaluation and treatment of patients with lymphedema. The management of chronic lymphedema continues to challenge both patients and treating physicians worldwide. In the past decades, however, substantial progress has been achieved for both diagnosis and therapy of these disabling conditions. With increasing attention to the quality of life, this debilitating life-long disease is receiving more attention not only by lymphedema specialists, but also by clinicians across the spectrum of health care delivery. Lymphedema: A Concise Compendium of Theory and Practice provides clear, concise background and recommendations in an easy-to-use format. It is a valuable reference tool for clinical practitioners (physicians/nurse practioners/technicians) who wish to deliver state-of-the-art health care to their patients with lymphatic and venous disorders.